PENGUNGKAPAN INFORMASI ASAL SUMBER DAYA GENETIK DALAM SISTEM HUKUM PATEN NASIONAL: KESENJANGAN NORMATIF DALAM AKSES DAN PEMBAGIAN MANFAAT - Emillia Isni Maulidina; Miranda Risang Ayu Palar; Laina Rafianti (Veritas et Justitia, 2026)
The increasing commercialization of inventions derived from genetic resources has intensified concerns regarding the disclosure of the origin of genetic resources and the effective implementation of the principle of access and benefit-sharing (ABS). Inadequate disclosure mechanisms risk facilitating the non-compliance with the obligation to disclose the origin of genetic resources and weakening legal certainty concerning the fair distribution of benefits arising from their utilization. This article examines the role of disclosure of origin requirements in strengthening the protection of genetic resources within Indonesia’s patent law framework. This study employs normative legal research methods to analyze the regulation and implementation of disclosure obligations concerning genetic resources in the national patent system. The findings reveal three principal issues. First, regulations governing genetic resources, particularly in the agricultural sector, have not adequately regulated benefit-sharing mechanisms, creating legal uncertainty for plant genetic resources used in patented inventions. Second, disclosure of origin functions as an important control mechanism for enforcing the principle of ABS within the patent system. While non-disclosure may impede the implementation of ABS obligations, it does not automatically establish a violation of those obligations. Third, failure to disclose accompanied by bad faith may justify patent revocation, particularly where genetic resources are intentionally concealed or misappropriated to secure exclusive patent rights. Accordingly, this research recommends reforming Indonesia’s patent law framework through the adoption of a legal provenance disclosure model.